Multidimensional poverty measurement and analysis - Alkire, Sabina; Foster, James E. (James Eric), 1955-; Seth, Suman; Santos, Maria Emma; Roche, José Manuel; Ballón, Paola (Oxford University Press, 2015)
A systematic conceptual, theoretical, and methodological introduction to multidimensional poverty measurement and analysis. It provides a lucid overview of the problems a range of multidimensional techniques can address and sets out a synthetic introduction of counting and axiomatic approaches to such measurement.